Effectiveness of Planned Teaching Program on Knowledge of Postnatal Mothers Regarding Care of Low Birth Weight Newborns in JK Lon Hospital, Kota (Rajasthan) - Kumar Meena, Mukesh; Sharma, Ravikant (International Journal of Nursing Research, 2023)
Background and Aim: The birth weight of an infant is the single most important determinant of its chances of survival, healthy growth, and development. One of the factors contributing to infant mortality is low birth weight (LBW). Aim: The aim of this study was to evaluate the effectiveness of planned teaching program on the care of LBW newborns among postnatal mothers of LBW newborns. Materials and Methods: An evaluative research approach with preexperimental design was used for the study. The study was conducted at JK Lon Hospital, Kota. The sample comprised 60 postnatal mothers of LBW newborns. Sample was selected using non-probability convenient sampling technique. Data were collected using a structured knowledge questioner. Data were analyzed using descriptive and inferential statistics. Results: The results of this study showed that the mean post-test knowledge score (87.62) also was higher than the mean pre-test knowledge score (48.67). The comparison of pre-test and post-test knowledge score showed that there was a significant gain in knowledge scores of mothers after PTP at 0.05 level (t-value = 16.994, P < 0.05). Interpretation and Conclusion: The findings of the study concluded that the planned teaching program on care of LBW newborns was highly effective in improving the knowledge of postnatal mothers regarding care of LBW newborns.